Efficacy of florfenicol for control of mortality associated with Francisella noatunensis subsp. orientalis in Nile tilapia, Oreochromis niloticus (L.) - Soto, E (Journal of fish diseases, 2013)
© 2012 Blackwell Publishing Ltd.